Development of Marbel Sitasya Interactive Learning Media Based on Canva to Improve Science Learning Outcomes - Rachma Selviana; Farid Ahmadi (Postgraduate, University of Mataram, 2024)
Study This developing learning media interactive based Canva provided​ term Marble Sitasya To use overcome problem low results study science material solar system in class VI Wonotulus State Elementary School Regency Purworejo. Study This use Research and Development ( RnD ) method with Borg and Gall stages. The data analysis technique uses a feasibility test product, initial and final data analysis namely the t test and the N-Gain test. Based on results study show that learning media very worthy used. This proven with results evaluation appropriateness products by media experts and expert material obtained percentage by 76% and 90%. This media is also effectiv used in accordance with t test results on both the test stage is the scale test small and test scale great showing​ results sig value. (2-tailed) is 0.000 < 0.05, meaning Ho is rejected and Ha is accepted. Besides Therefore, the N-Gain test results are obtained amounted to 0.51 on the scale test small and fruitful amounted to 0.6082 on the scale test big with criteria currently. based on results study this stated that learning media interactive Marble Sitasya based canva very feasible and effective for increase results study participant educate on science content material solar system in class VI Wonotulus State Elementary School Regency Purworejo.